Extending the Functional Cerebral Systems Theory of Emotion to the Vestibular Modality A Systematic and Integrative Approach. [article]. - Carmona, Joseph E..
Throughout history, vestibular and emotional dysregulation have often manifested together in clinical settings, with little consideration that they may have a common basis. Regarding vestibular mechanisms, the role of brainstem and cerebellar structures has been emphasized in the neurological literature, whereas emotion processing in the cerebral hemispheres has been the focus in psychology. A conceptual model is proposed that links research in the 2 desperate fields by means of a functional cerebral systems framework. The claim is that frontal region exert regulatory control over posterior systems for sensation and autonomic function in a dense, interconnected network. Impairment at levels within the system is expected to influence vestibular and cognitive process depending on the extent of frontal regulatory capacity, M. Kinsbourne's (1980) shared cerebral space model specifies the conditions under which dysfunction of the vestibular modality will influence higher cognitive levels. A position on laterality and associative relations within the right hemisphere is proposed to explain links among dizziness, nausea, and negative emotion. .-- (from the author)
Keywords: Emotion; Laterality; Vestibular system; Functional cerebral systems theory